2021
DOI: 10.1007/s11894-020-00801-2
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Endoscopic Ultrasound (EUS) in the Management of Gastric Varices

Abstract: Purpose of Review Gastric varices (GV) are an important complication of portal hypertension, and the current recommendation for management is beta-blocker therapy for primary prophylaxis and transjugular intrahepatic portosystemic shunt (TIPS) for active bleeding or secondary prophylaxis. Direct endoscopic injection of cyanoacrylate (CYA) glue has been investigated but has drawbacks including limited endoscopic characterization of GV and possible distal glue embolism. To this end, endoscopic ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 48 publications
0
24
0
4
Order By: Relevance
“…Almost all RCTs and meta-analyses reported numbers of adverse events from paracetamol that were inferior to those of NSAIDs and comparable to those of placebo. However, reviews on long-term observational data reported increased cardiovascular, gastrointestinal, and renal adverse events during therapy with paracetamol, especially in the high dose range; cases of acute liver failure have been reported after accidental and unintentional overdose of paracetamol [ 10 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 ]. Acute liver failure is infrequent with an approximate incidence for all causes of 1/million/year and is declining [ 134 ].…”
Section: Safety and Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Almost all RCTs and meta-analyses reported numbers of adverse events from paracetamol that were inferior to those of NSAIDs and comparable to those of placebo. However, reviews on long-term observational data reported increased cardiovascular, gastrointestinal, and renal adverse events during therapy with paracetamol, especially in the high dose range; cases of acute liver failure have been reported after accidental and unintentional overdose of paracetamol [ 10 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 ]. Acute liver failure is infrequent with an approximate incidence for all causes of 1/million/year and is declining [ 134 ].…”
Section: Safety and Toxicitymentioning
confidence: 99%
“…Furthermore, drug-induced liver injury is a diagnosis of exclusion that has been ascribed almost only to paracetamol [ 143 ]. However, a recent review indicates that a drug-induced liver injury is idiosyncratic, unpredictable, and related to herbal and dietary supplements and to a number of many potentially toxic drugs to the liver [ 144 ].…”
Section: Safety and Toxicitymentioning
confidence: 99%
“…According to some authors, EUS can evaluate ectopic duodenal varices [77], easily distinguish thickened gastric folds from small GV [78], and help in the diagnosis of portal gastropathy, showing diffuse thickening of the gastric wall with dilated paragastric veins (differential diagnosis to "watermelon stomach") [7]. EUS also has an important role in the characterization of GV, visualization of treatment in progress, and confirmation of obliteration using Doppler [79,80]. Furthermore, EUS can easily measure the size of GV, which directly correlates with their flow volume [81].…”
Section: Eus-guided Therapy For Phmentioning
confidence: 99%
“…Published online: 2021-05-31 nique [2][3][4][5]. This technique is feasible, simple, and may reduce the reported risk of reintervention compared with the combined (coil plus adhesive) strategy, avoiding the potential risks of using glue.…”
mentioning
confidence: 99%